1974
DOI: 10.1192/bjp.125.3.238
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Aberrations and LSD

Abstract: While the beneficial effect of lysergic acid diethylamide (LSD) in the treatment of carefully selected patients as an adjunct to psychotherapy has been amply reported (Robinson et al., 1963), concern has been expressed regarding the damage to chromosomes in those taking the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…This report could not stand up to meticulous scientific examination and was disproved by later studies (for example, Dishotsky [58] and for complete review Grof [31]). Empirical studies showed no evidence of teratogenic or mutagenic effects from use of LSD in man [59–61]. Teratogenic effects in animals (mice, rats, and hamsters) were found only with extraordinarily high doses (up to 500 μg/kg s.c.) [62].…”
Section: Pharmacology Of Lsdmentioning
confidence: 99%
“…This report could not stand up to meticulous scientific examination and was disproved by later studies (for example, Dishotsky [58] and for complete review Grof [31]). Empirical studies showed no evidence of teratogenic or mutagenic effects from use of LSD in man [59–61]. Teratogenic effects in animals (mice, rats, and hamsters) were found only with extraordinarily high doses (up to 500 μg/kg s.c.) [62].…”
Section: Pharmacology Of Lsdmentioning
confidence: 99%
“…In Untersuchungen, bei denen mit Leukozytenkulturen von Probanden, die LSD in halluzinogenen Dosen zu sich genommen haben, gearbeitet wurde, sind die In-vitro-Ergebnisse in bezug auf eine erhöhte Rate an Chromosomenaberrationen im Vergleich zu Kontrollgruppen verifiziert worden [10,15,16]. Im Gegensatz dazu zeigten sich in einer Studie mit Ratten sowohl bei der Mutter (Knochenmark) als auch bei den Embryonen keine chromosomalen Unterschiede zu den Kontrollen, obwohl hohe Dosen in mehrmaligen Applikationen verwendet wurden (500 Ìg/kg/Tag i.p.…”
Section: Risiken Bei Einnahme Während Der Schwangerschaftunclassified